Rancang Bangung Aplikasi Elektrokardiogram Yang Terintegrasi Dengan Picture Archiving And Communication System - Priyambodo, Fredy; Sutanto, Teguh; Romeo, Romeo (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
National Hospital is a modern private hospital of international standard established in 2010 in Surabaya. National Hospital wants to integrate existing modality cardiology section with its PACS. There are three main problems in the integration process, namely: (1) PACS that there can not display the data waveform (DICOM 3.0 supplement 30), (2) there is a modality resting ECG is not standard DICOM 3.0 so it can not communicate directly with PACS, and (3) resting ECG output data in XML format instead of 3.0 DICOM supplement 30. The solution to this problem is the application of ECG viewer that is integrated with PACS. ECG viewer application can handle communication from the modality DICOM 3.0 standard, namely ultrasound and treadmills, as well as from the resting ECG modality that is not standard DICOM 3.0. Further, the application of ECG viewer can convert XML data output from the resting ECG modality into DICOM 3.0 standard supplements 30 and make PACS can display a graphic waveform of the standard DICOM 3.0 file supmen 30.